Experimental and Numerical Investigation of Deep Drawing Process for Carbon Fiber Reinforced High Density Polyethylene (CF-HDPE) Composites - Ziedan, Mohammad Jameel; Hassan, Abdul Kareem Flaih; Saad, Najim A. (Basrah Journal for Engineering Sciences, 2025)
This study investigates the deep drawing process of carbon fiber-reinforced high-density polyethylene (CF-HDPE) composites through experimental and numerical approaches. The experimental part involved fabricating CF-HDPE sheets and conducting deep drawing operations under controlled parameters (punch speed, temperature, and forming depth) to evaluate material behavior and mechanical properties. Numerically, finite element analysis (FEA) using ABAQUS simulated the forming process, analyzing stress distribution, strain development, and material deformation under varying conditions. Results revealed that increasing forming depth and decreasing forming temperature elevated the required forming force. Comparisons between experimental and numerical outcomes showed consistent trends, though some differences arose due to factors like friction and material nonlinearity. The findings contribute to optimizing deep drawing processes for composite materials, enhancing manufacturing precision, and minimizing material defects.